2021
DOI: 10.1101/2021.04.12.21255330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of natural SARS-CoV-2 infection in seroprevalence studies among vaccinated populations

Abstract: Importance: Identification of SARS-CoV-2 infection via antibody assays is important for monitoring natural infection rates. Most antibody assays cannot distinguish natural infection from vaccination. Objective: To assess the accuracy of a nucleocapsid-containing assay in identifying natural infection among vaccinated individuals. Design: A longitudinal cohort comprised of healthcare workers (HCW) in the Minneapolis/St. Paul metropolitan area was enrolled. Two rounds of seroprevalence studies separated by one m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated this protein is highly immunogenic and plentiful, with antibodies directed against it being more sensitive to early infection detection than antibodies targeting the spike protein (Burbelo et al, 2020). In addition, detecting anti-N antibodies allows differentiating individuals vaccinated with S-directed vaccines based on the history of infection (Demmer et al, 2021). IgG directed against the N protein can indicate both symptomatic and asymptomatic SARS-CoV-2 infection and vaccination with the BBIBP-CorV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated this protein is highly immunogenic and plentiful, with antibodies directed against it being more sensitive to early infection detection than antibodies targeting the spike protein (Burbelo et al, 2020). In addition, detecting anti-N antibodies allows differentiating individuals vaccinated with S-directed vaccines based on the history of infection (Demmer et al, 2021). IgG directed against the N protein can indicate both symptomatic and asymptomatic SARS-CoV-2 infection and vaccination with the BBIBP-CorV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DBS collection and anti-IgG serology show promise as a tool to measure SARS-CoV-2 seropositivity at the population level. The benefits include comparable diagnostic accuracy to that of serum samples, with improved population reach and the potential to discriminate natural from vaccine-elicited seroconversion by measuring anti-S and anti-N IgG reactivity in a single reaction ( 20 ). In a theoretical population with 75% COVID-19 seroprevalence, a positive DBS-MSD result reliably indicates seropositivity with a high PPV and does not require additional testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DBS collection and anti-IgG serology shows promise as a tool to measure SARS-CoV-2 seropositivity at the population level. The benefits include comparable diagnostic accuracy to that of serum samples, with improved population reach, and the potential to discriminate natural from vaccine elicited seroconversion by measuring anti-S and anti-N IgG reactivity 14 . In a theoretical population with seventy-five percent COVID-19 vaccine coverage, a positive DBS-MSD result reliably indicates seropositivity with a high PPV and does not require additional testing.…”
Section: Discussionmentioning
confidence: 99%